The Challenges of Teaching English for Economics - Sartorio, Siham; Hamitouche, Fatiha (المركز الجامعي أمين العقال الحاج موسى أق أخموك لتامنغست - معهد الحقوق والعلوم السياسية, 2021)
هدفت الدراسة الحالية إلى اكتشاف الصعوبات والعراقيل التي يواجهها كل من أساتذة الإنجليزية والطلبة في كلية العلوم الاقتصادية والتجارة والتسيير بجامعة غرداية والتي تحول دون نجاح العملية التعليمية والأداء الجيد للطلبة في اللغة الإنجليزية. أجريت الدراسة مع عينة متكونة من 5 أساتذة للإنجليزية المتخصصة و99 طالباً من أقسام مختلفة بالكلية. أظهرت النتائج أن الإنجليزية المتخصصة تواجه جملة من التحديات والصعوبات من بينها: عدم وجود منهاج نقص تدريب أساتذة نقص موارد التدريس نقص تحفيز الطلاب العدد الكبير للطلبة بالأفواج وساعات التدريس غير الكافية.
The aim of the present paper is to shed light on the major problems and barriers that hinder successful ESP teaching/ learning in the Algerian University. It reports the findings of a study conducted at the faculty of Economic Sciences, Commerce and Management of the University of Ghardaia with a sample of 5 ESP teachers and 99 students enrolled at different departments across the faculty. Classroom observation and two questionnaires were used for data collection. The results revealed that ESP is facing many challenges in our universities among them: the lack of ESP syllabus, lack of ESP teacher training, lack of teaching resources, lack of students" motivation, large classes and insufficient instruction hours.
Keywords: تدريس اللغة الإنجليزية -- اللغة الإنجليزية لأغراض متخصصة -- علم الاقتصاد -- التعليم الجامعي